2020
DOI: 10.21203/rs.3.rs-52091/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Koala Retrovirus Diversity, Transmissibility, and Disease Associations

Abstract: Background Koalas are infected with the koala retrovirus (KoRV) that exists as exogenous or endogenous viruses. KoRV is genetically diverse with co-infection with up to ten envelope subtypes (A-J) possible; KoRV-A is the prototype endogenous form. KoRV-B, first found in a small number of koalas with an increased leukemia prevalence at one US zoo, has been associated with other cancers and increased chlamydial disease. To better understand the molecular epidemiology of KoRV variants and the effect of increased … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…KoRV-A infections in southern animals may represent genuine exogenous (infectious) virus as these are in many cases also present at less than one copy per genome equivalent [5]. The non-A variants may also represent genuine exogenous (infectious) virus in both northern and southern animals, circulating independently with these present as low copy number/somatic insertions [22,33,34], not detected in all animals [24,25,29,[35][36][37] and display a pattern of detection in family groupings consistent with a maternally transmitted infection [28,35,37,38]. Some caution is necessary in interpreting this however as phylogenetic analysis of the envelope variants from a variety of sequencing studies do not clearly indicate chains of transmission [29,31,36].…”
Section: Introductionmentioning
confidence: 99%
“…KoRV-A infections in southern animals may represent genuine exogenous (infectious) virus as these are in many cases also present at less than one copy per genome equivalent [5]. The non-A variants may also represent genuine exogenous (infectious) virus in both northern and southern animals, circulating independently with these present as low copy number/somatic insertions [22,33,34], not detected in all animals [24,25,29,[35][36][37] and display a pattern of detection in family groupings consistent with a maternally transmitted infection [28,35,37,38]. Some caution is necessary in interpreting this however as phylogenetic analysis of the envelope variants from a variety of sequencing studies do not clearly indicate chains of transmission [29,31,36].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the disease association of the other exogenous subtypes. One study in captive koalas found that the non-KoRV-A subtypes may be associated with increased cancer rates [ 31 ]. By contrast, KoRV-D expression levels have been found to be higher in healthy koalas compared to those that developed Chlamydial disease [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of KoRV subtype, higher levels of KoRV viremia are expected to be associated with disease. Indeed, in three koala cohorts studied [ 31 , 33 35 ] an association between plasma viral load and neoplasia has been found. However, in the case of secondary diseases, previous studies have produced mixed findings.…”
Section: Introductionmentioning
confidence: 99%